2019
DOI: 10.1111/1759-7714.13172
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary synovial sarcoma with calcification: A case report

Abstract: The lung is the organ most commonly affected by primary synovial sarcoma. Intratumoral calcification is less common in this organ versus soft tissue. Meanwhile, the presence of calcification in a lung nodule reduces the risk of lung cancer. Here, we report a case of pulmonary synovial sarcoma which manifested as a nodule with calcification, depicted on computed tomography (CT). A 52‐year‐old asymptomatic male was referred to Saitama Medical University International Medical Center and CT revealed a well‐defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The MDT considered that these tumors were SS before the operation and pathologically confirmed the diagnosis after the operation. Previous studies have reported that calcifications may occur in a few tumors (11,13). In our study, some patients were also found to exhibit calcifications in their tumors.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The MDT considered that these tumors were SS before the operation and pathologically confirmed the diagnosis after the operation. Previous studies have reported that calcifications may occur in a few tumors (11,13). In our study, some patients were also found to exhibit calcifications in their tumors.…”
Section: Discussionsupporting
confidence: 68%
“…The challenge of diagnosing and treating primary intrathoracic SS (13) is mainly the result of the location of the tumor and the difficulty of the operation, which requires a safe margin around the soft tissue tumor (generally ensuring that the normal tissue at least 2 cm away from the tumor edge is removed). Therefore, multidisciplinary partnerships are particularly important for discussing diagnosis and treatment plans.…”
Section: Introductionmentioning
confidence: 99%
“…For about 30% of cases, calcification may. [ 12 ] Another significant clinical finding is that PRSS may appear on the CT scan as a mass with calcification. Although the exact reason is still uncertain, these characteristics may be related to its histological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…On the imaging findings of CT, PPSS usually shows soft‐tissue mass and pleural mass with round or lobulated boundary, with clear boundary and irregular enhancement 24,25 . It may also be shown as small nodules and occasionally accompanied by calcification 26 . Enhanced CT shows the degree of blood triple density of vascular influence tube 27 .…”
Section: Discussionmentioning
confidence: 99%
“…24,25 It may also be shown as small nodules and occasionally accompanied by calcification. 26 Enhanced CT shows the degree of blood triple density of vascular influence tube. 27 MRI generally shows low-signal intensity on T1-weighted images, with or without highsignal areas indicating bleeding.…”
Section: Discussionmentioning
confidence: 99%